2014
DOI: 10.5336/medsci.2012-33284
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tamsulosin on the Anterior Segment Parameters and Central Corneal Thickness

Abstract: To in ves ti ga te the ef fects of tam su lo sin (α-1 ad re ner gic re cep tor an ta go nist) on the ma in nu me ri cal pa ra me ters of an te ri or seg ment using Pen ta cam ro ta ting Sche immp flug came ra, and on bi o mec ha ni cal pa ra me ters using Re ic hert Ocu lar Res pon se Analy ser (ORA) in pa tients with be nign pros ta te hyperp la si a. M Ma a t te e r ri i a al l a an nd d M Me et t h ho od ds s: : In ad di ti on to full eye exa mi na ti on [best cor rec ted vi su al acu ity, ke ra to metry, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…A recent study by Storr-Paulsen et al showed that endothelial cell loss after cataract surgery in patients with IFIS are more pronounced. 3 CCT increment in these patients group after tamsulosin therapy with no history of any surgical procedure was also demonstrated by Palamar et al 5 These data support that not only iris and pupillae but also corneal tissue might also be involved by tamsulosin use.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…A recent study by Storr-Paulsen et al showed that endothelial cell loss after cataract surgery in patients with IFIS are more pronounced. 3 CCT increment in these patients group after tamsulosin therapy with no history of any surgical procedure was also demonstrated by Palamar et al 5 These data support that not only iris and pupillae but also corneal tissue might also be involved by tamsulosin use.…”
Section: Discussionsupporting
confidence: 72%
“…Palamar et al recently reported the increment on CCT after 1 month of tamsulosin use. 5 ORA is a new non-contact tonometer developed by Reichert, that measures IOP and new metrics, CH and CRF. It uses a metered collimated air pulse to applanate the cornea and an infrared electro-optical system to record inward and outward applanation events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported that patients taking tamsulosin had not only a sluggish iris, but also a small pupil diameter, both making cataract surgery more challenging (2, 3). In 2012, we evaluated changes in anterior segment parameters as measured with the Pentacam rotating Scheimpflug camera (anterior chamber depth, anterior chamber volume, anterior chamber angle width, and pupillary diameter) and corneal biomechanical parameters with the Reichert ocular response analyzer (ORA) (corneal hysteresis, corneal resistance factor) in patients with benign prostate hyperplasia after tamsulosin intake (4). We found that central corneal thickness significantly increased after 1 month of tamsulosin use.…”
mentioning
confidence: 99%
“…We found decreased anterior chamber depth (ACD), anterior chamber volume (ACV), anterior chamber angle (ACA) width, and pupil diameter (PD) values in the tamsulosin and doxazosin groups when compared to controls. Palamar et al (2) evaluated patients 1 month after tamsulosin treatment. They did not find any changes in ACD, ACV, ACA width, or PD.…”
mentioning
confidence: 99%